Refinement of SARS-CoV-2 envelope protein structure in a native-like environment by molecular dynamics simulations - Yang, Rui; Wu, Sijin; Wang, Shen; Rubino, Grace; Nickels, Jonathan D.; Cheng, Xiaolin (Frontiers in Molecular Biosciences, 2022)
COVID-19 has become an unprecedented threat to human health. The SARS-CoV-2 envelope (E) protein plays a critical role in the viral maturation process and pathogenesis. Despite intensive investigation, its structure in physiological conditions remains mysterious: no high-resolution full-length structure is available and only an NMR structure of the transmembrane (TM) region has been determined. Here, we present a refined E protein structure, using molecular dynamics (MD) simulations to investigate its structure and dynamics in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayer system. Our initial homology model based upon the SARS-CoV E protein structure is shown to be unstable in the lipid bilayer, and the H3 helices tend to move away from the membrane center to the membrane-water interface. A more stable model was developed by replacing all H3 helices with the fully equilibrated H3 structure sampled in the MD simulations. This refined model exhibited more favorable contacts with lipids and water than the original homology model and induced local membrane curvature, decreasing local lipid order. Interestingly, the pore radius profiles showed that the channel in both homology and refined models remained in a closed state throughout the simulations. We also demonstrated the utility of this structure to develop anti-SARS-CoV-2 drugs by docking a library of FDA-approved, investigational, and experimental drugs to the refined E protein structure, identifying 20 potential channel blockers. This highlights the power of MD simulations to refine low-resolution structures of membrane proteins in a native-like membrane environment, shedding light on the structural features of the E protein and providing a platform for the development of novel antiviral treatments.